Panoramic atrial mapping with basket catheters: A quantitative analysis to optimize practice, patient selection, and catheter choice. (26th September 2017) - Honarbakhsh, Shohreh; Schilling, Richard J.; Providência, Rui; Dhillon, Gurpreet; Sawhney, Vinit; Martin, Claire A.; Keating, Emily; Finlay, Malcolm; Ahsan, Syed; Chow, Anthony; Earley, Mark J.; Hunter, Ross J.
Abstract: Introduction: Panoramic mapping with basket catheters has been used to map atrial fibrillation (AF). However, the limited tissue contact and coverage achieved has raised concerns. Methods and Results: Patients undergoing catheter ablation for atrial tachycardia (AT) and persistent AF were recruited. Unipolar signals were recorded with the Constellation or FIRMap catheters. The proportion and distribution of anatomical coverage by the catheters was determined and tissue contact achieved measured. The impact of catheter position, left atrium (LA) size, and bipolar voltage were evaluated. Forty patients were recruited (20 Constellation and 20 FIRMap). The LA coverage achieved with the FIRMap catheter compared to the Constellation catheter was greater (76.9 ± 12.9% vs. 50.8 ± 10.3%; P < 0.001), with better septal coverage (66.8 ± 20.9% vs. 15.5 ± 12.0%; P < 0.001). A greater number of electrodes recorded peak‐to‐peak electrogram amplitude of ≥0.5 mV (84.2% vs. 62.8%; P < 0.001). Positioning the catheter tip at or posterior to LA appendage ridge gave better coverage than a more anterior position (P = 0.001). Increasing LA area correlated inversely with coverage (P < 0.001) and contact (P = 0.002) despite patient‐specific basket catheter sizing. An LA area of >30 cm 2 and mean bipolar voltage of <0.3 mV was associated with reduction in coverage and contact (both P < 0.001). There was a significant difference in AT/AF freedom during follow‐up in the FIRMap versus Constellation group (13/13 vs. 8/12; P = 0.04). Conclusions: The FIRMap is superior to the Constellation catheter in terms of LA coverage and contact. Optimizing catheter position and appropriate patient selection based on no more than moderately dilated or scarred atria will also facilitate mapping with basket catheters.